An Orange‐Emitting Phosphorescent Iridium(III) Complex Featuring Three Strong Electron‐Donating N‐Embedded π‐Conjugation Units. Issue 20 (20th May 2022) - Song, Jialiang; Li, Feiyang; Shi, Chao; Li, Gang; Liu, Xinyu; Wu, Meng; Zeng, Ruoqi; Li, Qiuxia; Zhao, Qiang; Yuan, Aihua
Abstract: We firstly design and synthesize a new facial phosphorescent iridium complex fac ‐Ir (NO )3 with three strong electron‐donating N‐embedded π‐conjugation units. It is found that the complex fac ‐Ir (NO )3 can display a distinct orange phosphorescence emission (λ=582 nm) with a redshift of 55 nm relative to model complex fac ‐Ir (N )3 (λ=527 nm) with three triphenylamine units. Notably, it also exhibits a significantly narrower half‐peak width (FWHM=70 nm) compared with model complex Ir (NO )2 acac (FWHM=97 nm) with two N‐embedded π‐conjugation units. In addition, it also shows both distinct intraligand charge transfer (ILCT) and partial unusual ligand‐to‐metal charge transfer (LMCT) excited state properties due to strong electron‐donating capacity of three N‐embedded π‐conjugation units. Abstract : A new facial phosphorescent iridium complex fac ‐Ir(NO )3 with three strong electron‐donating N‐embedded π‐conjugation units has been prepared. It can display a distinct orange phosphorescence emission with a narrow half‐peak width. In addition, it also shows both distinct intraligand charge transfer (ILCT) and partial unusual ligand‐to‐metal charge transfer (LMCT) excited state properties due to strong electron‐donating capacity of three N‐embedded π‐conjugation units.